(untitled) (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Focal task-specific dystonia of the hand is unusual in childhood. Childhood dystonia can result in lifelong disability and thus represents a significant diagnostic and rehabilitation challenge. A detailed clinical evaluation and comprehensive work-up to rule out treatable causes of focal dystonia are mandatory for establishing a therapeutic strategy. We reported 4 cases of writer. s cramp with earliest age of onset. Our aim was to focus on early detection, proper evaluation and management of writer’s cramp to ensure better quality of life of an affected child. J Com Med Col Teachers Asso Jan 2024; 28(1): 33-36